Hermenêutica Constitucional do princípio da função social da propriedade: desencontros da atuação do Poder Judiciário da Comarca da Ilha de São Luís à luz das decisões do Superior Tribunal de Justiça e do Supremo Tribunal Federal no exercício da jurisdição constitucional democrática - MORAES, Vitor Hugo Souza (2022)
This research problematizes the performance of the Judiciary in the analysis of the possessory conflicts of collective and consolidated nature in the County of the Island of São Luís meets the hermeneutic expectations of the STJ and STF and a democratic constitutional jurisdiction compatible with the challenges of a free, fair and solidary society as constitutive elements of human dignity. At first, considerations about the methodological path of the research are presented, situating it in the bibliographic and documentary analysis of the exploratory type, quantitative and qualitative approach, inductive reasoning and content analysis according to Bardin, used to codify, categorize and analyze the object of research: the repossession judicial decisions rendered in the face of consolidated collectivities in the County of the Island of São Luís, by the state justice of first degree, during the years 2017 to 2020. The hypothesis is that the judicial decisions analyzed do not observe the principle of the social function of the property when determining the repossession of collective occupations, contrary to the understanding of the STF and STJ and the concept of constitutional jurisdiction. The research is structured around the general objective of analyzing the application of the principle of the social function of property in judicial decisions in collective possession disputes and its correspondence to the expectations of the democratic constitutional jurisdiction, and the specific objectives of making a critical study of the social function of property and the constitutionalization of civil law; Finally, to collect and analyze the content of the object of the research, we seek to explore judicial action in collective possession disputes concerning the adequacy of the reasoning of the decisions to the constitutional jurisdiction and the protection of the rule of law. Based on the results collected, the hypothesis is confirmed, confirming that the decisions analyzed are not appropriate for constitutional jurisdiction and, for the most part, do not observe the procedural and procedural parameters that are appropriate for resolving collective disputes over land. The development of the research adopted the theoretical framework of Law as Integrity (Dworkin) and in dialogue with the contributions of Klaus Günther and Cássius Chai on legal hermeneutics, and brings the general conclusion of the need for the grounds of the judicial decisions to be adequate to the constitutional jurisdiction, to the hermeneutic model of the Superior Courts and to the procedures determined in the CPC, to guarantee the jurisdictional provision compatible with the defense of the Rule of Law.